Supply Chain Risk Management and Frameworks in the UK Industry - Chan, Ratanak (2011)
This research aims to study the supply chain risk management in the retail industry. The risen in level of risks in the supply chain and the increasing role of retailers in the supply chain have driven this research to be conducted. Four important objectives of this research are: to identify and categorise retail supply chain risks, to present which principal risks have been concerned by most retailers, to build the supply chain risk mitigation framework in the retail supply chain, and to discuss the role of retailers in mitigating supply chain risks. Methods used to achieve the objectives are: reviewing academic literatures, studying 60 UK retailers by collecting data from their annual reports, and use published case studies to gain a deeper insight of a particular topic.